Nieznane poglądy sędziego Bohdana Winiarskiego na zagadnienie obywatelstwa i opieki dyplomatycznej - Skubiszewski, Krzysztof (Wydział Prawa i Administracji UAM, 1987)
Judge Winiarski was unable to take part in the last stage of the second phase of the Nottebohm case decided by the International Court of Justice in 1956. He was thus prevented from appending to the judgement his dissenting opinion. He subsequently wrote down a statement of his views, dated 15th June 1955, and circulated it among the members of the Court and some other jurists. The present contribution briefly presents Judge Winiarski's unpublished views against the background of the Court's judgement. Friedrich Nottebohm was German by birth domiciled in Guatemala. In 1939 he acquired the nationality of Liechtenstein. The Court found that the naturalization conferred on Nottebohm could not be invoked by Liechtenstein against Guatemala, and Liechtenstein was not entitled to exercise its protection in favour of Nottebohm against Guatemala. Consequently, the Court held that the claim submitted by Liechtenstein was inadmissible. Judge Winiarski disagreed. According to him, between 1940 and 1944 the Government of Guatemala regarded Nottebohm as a national of Liechtenstein, and — as a result — an official relationship arose between the two Governments. That relationship concerned the right of diplomatic protection. The naturalization of Nottebohm by Liechtenstein was lawful, while the Hague Court cannot pronounce on the interpretation and application of municipal law when done by the supreme organs of the country. Each country decides on the regularity of the naturalization brought under its laws, and the naturalization of Nottebohm remained within the domestic jurisdiction of Liechtenstein, though Judge Winiarski did not deny that there might be situations where naturalization was governed by treaties or other rules of international law. Nor did Nottebohm solicit the Liechtenstein nationality fraudulently. Having established that the naturalization of Nottebohm was valid in both municipal and international law Judge Winiarski criticized the Court for not admitting that Liechtenstein had the right to exercise its diplomatic protection with regard to Nottebohm. Any non-recognition of nationality and of the resulting right of diplomatic protection could only be based on reasons that follow from international law. The concept of effective nationality and the concept of the real connection with the naturalizing State were of strictly limited relevance in international law. Various factors adduced by the Court in this context were not conclusive in law. In particular, they did not follow from international law and were too subjective to find support in judicial decisions. In Judge Winiarski's opinion the Court's judgement went beyond positive law. Judge Winiarski also criticised the "unexpected formalism" of the Court in considering it unnecessary to have regard to certain new documents filed after the closure of the written proceedings. The Court thus deprived itself of the possibility of verifying some further facts that were alleged. The examination of these facts could have thrown new light on the admissibility of the claim submitted by Liechtenstein. Judge Winiarski thought that the Court should have adjourned the oral proceedings.
The unknown views of judge Winiarski on questions of nationality and diplomatic protection